Deciphering Nitrogen Stress Responses in Maize Rhizospheres: Comparative Transcriptomics of Monocropping and Intercropping Systems - Bing Zhang; Jamal Nasar; Siqi Dong; Guozhong Feng; Xue Zhou; Qiang Gao (Agronomy)
A well-developed rhizospheric system is crucial for maize to adapt to environmental stresses, thereby enhancing yield and quality. However, nitrogen (N) stress significantly impedes rhizospheric development and growth in maize. The genetic responses of maize’s rhizosphere to N stress under monocropping systems with exogenous inorganic N fertilization and intercropping systems reliant on biological N fixation are not well understood, especially regarding common and specific response genes. Therefore, through transcriptomic analysis, this study systematically investigated the gene expression and molecular responses of maize’s rhizosphere under two N supply regimes to N stress. The results showed that N stress generated 196 common and 3350 specific differentially expressed genes across the two systems, with the intercropping system exhibiting a stronger specific response. KEGG analysis revealed that the common genes, though few, are involved in key pathways essential for crop growth. Maize monocropping specific differentially expressed genes (MM) were enriched in pathways related to membrane lipids, cell wall formation, and intracellular signaling, while maize/alfalfa intercropping specific differentially expressed genes (MA) were linked to stress resistance through the glutathione metabolic pathway. WGCNA analysis identified five co-expression modules (CM). MA significantly increased the transcription factor families and structural domains directly targeting rhizospheric growth and development genes, including AP2, GRAS, Cys2His2 Zinc Finger, and LBD in CM blue. Conversely, MM significantly increased the transcription factor families and NAC structural domain targeting the promoters of N transporter protein genes in CM pink. This study emphasizes the importance of both common and specific genes in maintaining maize growth under suboptimal N supply in monocropping and intercropping systems.